2005
DOI: 10.1111/j.1365-2929.2005.02190.x
|View full text |Cite
|
Sign up to set email alerts
|

How medical residents perceive the quality of supervision provided by attending doctors in the clinical setting

Abstract: This study shows that medical residents enjoy supervision from collaborative, understanding and patient attending doctors. Medical residents prefer to be treated as adult learners and enjoy feedback that is constructive, measured and adapted to their professional needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 20 publications
3
76
0
1
Order By: Relevance
“…Busari et al 3 have offered a glimpse of residents' views regarding supervision. Their survey of 38 pediatric residents found that most residents in their study rated the supervision they received favorably.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Busari et al 3 have offered a glimpse of residents' views regarding supervision. Their survey of 38 pediatric residents found that most residents in their study rated the supervision they received favorably.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Recent narrative studies have suggested that a collaborative approach to supervision, coupled with constructive feedback, is preferred by trainees. 12 Kennedy and colleagues 13 described a conceptual model for clinical oversight, ranging from monitoring routine activities to intervening to provide direct patient care. However, there is currently no effective model describing clinical supervision in internal medicine residency training that addresses both the role of the attending or supervising physician and the resident physician in the supervisory relationship.…”
mentioning
confidence: 99%
“…providing and progressively withdrawing support as appropriate), encouraging learners to articulate their thinking, encouraging learners to reflect on their experiences and helping learners to explore and pursue their learning goals. [3][4][5][6] In practice, however, the provision of clinical supervision has been found to be suboptimal and highly variable from one setting to the next, even in the critical task of providing constructive feedback based on observations of learner performance. [6][7][8] Improving the current state of affairs requires an examination of its root causes.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of time is a commonly cited environmental constraint and a difficult one to tackle, requiring institutional-level interventions. 6,10,11 Insufficient knowledge and skills have also been identified 6,8,10,12 figure 1 The integrative model of behaviour prediction. Adapted from Fishbein 9 involved in teaching with medical students and/or residents also suggest that issues of beliefs and identity are relevant to the provision of good clinical teaching.…”
Section: Introductionmentioning
confidence: 99%